Reifying “river”: Unpacking pluriversal possibilities in rejuvenation surrounding the Adi Ganga of Kolkata - Bhattacharya, Shreyashi; Mukherjee, Jenia; Choudry, Anuradha; Ghosh, Raktima (Frontiers in Water, 2023)
Using the River Adi Ganga as the case study and implementing the historical urban political ecology (HUPE) framework, we demonstrate multiple trends and trajectories that comprise city-river relationships,to explore coeval ontologies framing ‘river’, ‘riverine space’ and ‘river rejuvenation’ schemes, awaiting accommodation in urban environmental planning and water/river management. We have encapsulated ‘storylines’ through the deployment of multi-modal (qualitative) research methodologies to trace and document plural perceptions on the river that was declared to be ‘dead’, especially the particular stretch that was pillaged with the construction of the metro pillars (directly obstructing her flow. Media journalists and activists narrative that this act had slaughtered the river and robbed her of her original flows and services crafted a deep imprint on the citizens of Kolkata who consider the river as a stinking sink, offering minimal sewerage facilities to the city. Our paper challenges this linear depiction and weaves together positive moments, events and actions that keep the river flowing – shaping and in turn being shaped by (more-than)human actors across long temporal units and scales. We integrate the numerous agential and stakeholder voices attached to the river, shedding light on various (un)successful attempts to revive the river beyond global conceptualizations of what a ‘river’ should be. We believe that the unfolding of this ‘pluriverse’ (Escobar 2011) will forge sustainable understandings of the river’s current challenges and existing opportunities towards a collaborative blueprint through knowledge coproduction, stakeholder mobilization and actions. While our empirical frame of reference focuses on micro-realities surrounding a particular river on a specific urban hydroscape, our theoretical-conceptualization framings and methodological applications will have potentials to be implemented at scales.